Nonsingular fractional-order integral fast-terminal sliding mode control for underactuated shipboard cranes - Cuong, Hoang Manh; Thai, Nguyen Van; Trieu, Pham Van; Dong, Hoang Quoc; Nam, Tran The; Viet, Tran Xuan; Nho, Luong Cong; Tuan, Le Anh (Journal of the Franklin Institute, 2022)
Lack of actuators creates many challenges in controlling underactuated systems. Additional difficulty arises when underactuated systems are subject to actuator faults, parametric uncertainties, and disturbances. We develop an adaptive robust controller for such systems by combining various advanced techniques with many benefits. The core of the controller, which is based on nonsingular integral fast-terminal sliding mode, ensures high robustness and quick finite-time convergence, reduces chattering, and prevents singularity. Fault-tolerant control provides good fault compensation. Fractional derivatives make the control structure flexible because fractional orders are adjustable gains. Self-tuning control creates an adaption mechanism that endows the system an intelligent behavior. Two layers of the sliding mode that contain fractional derivative, terminal power, and definite integral ensure terminal Mittag–Leffer stability. We test the proposed approach on an underactuated floating crane through a simulation and an experiment. A comparison with other methods shows the superiority of our approach.